Quantum Dot Solar Cells with size tuned CdSe QDs exhibiting 1.51V. (2018) - Surana, Karan; Mehra, R.M.; Bhattacharya, Bhaskar
Abstract: Over the past few years quantum dots have gained popularity in various arenas of science and technology, one such being their use as sensitizers in quantum dot solar cells (QDSC). Owing to their larger available surface area, multiple exciton generation capability and size dependent optical properties, the probability of developing superior performance solar cells increases. Despite their advantages the efficiency of quantum dot sensitized solar cells is still far from taking it into commercial production. Out of the many responsible factors one is the inefficient transfer of electrons through the mesoporous semi-conductor layer. In this paper we have reported the assembling of CdSe QDs, tuned for photon trapping at different wavelengths in order to achieve an optimum band alignment for better charge transfer in QDSC.